Corrosion Modelling with Cellular Automata - Feron, Damien; Feron, Damien; Dung, Di Caprio (Woodhead Publishing, 2024)
Corrosion Modelling with Cellular Automata bridges the gap between finer scales based on atomic physics and the larger-scale based on physico-chemical properties of materials and their environments. The book describes the simulation and modeling of corrosion phenomena by cellular automata and underlines the collaborative and interdisciplinary relationships that underpin them. It explores the major achievements that have been performed to date, covers basic knowledge on cellular automata and corrosion phenomena, and includes sections on CA modeling of generalized and uniform corrosion in 2D and 3D under various conditions, including aqueous environments and high temperature processes. Finals sections present examples on the use of cellular automata for modeling localized corrosion as well as recent developments on intergranular corrosion. There is also a review on the use of CA for modeling pitting corrosion. - Focuses on the use of cellular automata for modeling corrosion - Covers recent advances in modeling generalized corrosion with cellular automata - Illustrates how cellular automata can be used to model localized corrosion (pitting and intergranular corrosion) - Spans various length scales from atomistic to mesoscale